Agreement for The Sale and Purchase of Goods Internationally According to the CISG and the Civil Code - Silfiyana Salsabillah (Jurnal Justiciabelen, 2025)
In international trade, transactions will always be related to contracts. It's not easy to connect agents in international business. this relates to differences in national legal systems, paradigms, and regulations that have been established as enforcement of rules that must be obeyed by agents of each country. By unifying the existence and alignment of regulations and practices through several efforts, namely CISG for Indonesia in the Indonesian Civil Code (KUHPerdata) which is expected to reduce the differences between Indonesian barriers and for the same point of view which can make it easier for agents to fulfill legal requirements in international transactions of approval. Setting rights and obligations between sellers and buyers in international transaction agreements, entering into international transaction agreements with agents and cost compensation systems affect the non-fulfillment of transaction agreements based on CISG and Civil Law.